Problems of State Regulation of the Russian Labor Market - R. Fatkhutdinova, Leysan; V. T, Viktoriia; I. Zhuk, Sergey (International Journal of Engineering and Technology, 2026)
In the given article the problem of regulation of the Russian labor market by the state is considered. It is the state that can and should create conditions for the country's effective social and economic development. The main tool for the implementation of this function is the labor market. To clarify this provision, in this paper, an analysis of the report on the implementation of measures to prevent labor market tension in 34 regions and 91 mono-profile settlements of the Russian Federation for 2016, compiled during the implementation of the state program of the Russian Federation "Promotion of employment of the population".  The growth of unemployment causes quite a strong strain on the labor market. This is a very difficult and important problem for the country's socio-economic development. Another factor of tension in the labor market is the deficit of many specialties, in particular in health care, in science intensive industries, and skilled workers and middle-level specialists. In this regard, the work analyzes statistical data on the number and structure of graduates of various educational institutions in the areas and specialties. In general, the structure of training bachelors, specialists and masters should be more balanced.
Keywords: Labor market; demand for labor; labor supply; qualification; investment in human capital; labor market tension.